The ammonoids from the Gattendorfia Limestone of Gattendorf (Devonian–Carboniferous boundary; Upper Franconia, Germany) - Korn, Dieter; Weyer, Dieter (European Journal of Taxonomy, 2023)
The early Tournaisian (Early Carboniferous; Mississippian) ammonoids from the classical abandoned limestone quarry of Gattendorf (Upper Franconia) are revised, using the historical collections as well as so far undescribed material. The ammonoid assemblage is composed of prionoceratid ammonoids of the six genera Mimimitoceras, Paragattendorfia, Stockumites, Acutimitoceras, Gattendorfia and Gattenpleura, which indicate a stratigraphic position near the Devonian–Carboniferous boundary in the earliest Carboniferous. The new species Stockumites hofensis sp. nov. and S. nonaginta sp. nov. are described.